Trapping parasite secretory proteins in baker's yeast - Nene, Vishvanath M.; Bishop, Richard P. (Elsevier, 2001)
Because the function of signal sequences has been conserved during evolution it has been possible to develop both bioinformatics resources to identify them and techniques to clone genes that encode secretary proteins. The latter entail insertion of heterologous signals upstream of signal peptide deleted reporter genes. We discuss the advantages of using Saccharomyces cerevisiae for signal sequence trap technology. The yeast protein-translocation system appears to be less discriminating than that of higher eukaryotes - for example, a Theileria parva cysteine protease gene containing a recessed, nonclassical signal allows access to the secretary pathway- and yeast technology could have general application in studying elements of parasite protein trafficking.